Long Term Changes in Rotifera fauna of Guluskur Bay (Keban Dam Lake Elazig Turkey) - Saler, Serap; Sen, Bulent (Medwell Online, 2010)
Rotifera species and their seasonal variations were investigated together with some physical and chemical parameters of water. Samples were taken monthly between October 1996-September 1998 and January 2008-December 2008 revealed some chemical and physical characteristics. In the first sampling period 27 Rotifer species and in the second sampling period 24 Rotifer species were recorded. In both sampling periods increases were occurred in individual and taxon numbers of rotifers in spring and summer seasons. In the first and second sampling periods Keratella cochlearis and Polyarthra vulgaris were the most abundant species. The purpose of this investigation was to describe the species composition of rotifera and to compare two sampling periods results in order to determine how structure of rotifer populations has changed in past 10 years. In comparison with two sampling periods, some changes have been taken place in the composition of rotifers. The high species richness of rotifers; particularly members of the genera Brachionus suggested that the lake probably eutrophicated.
Keywords: Long-term; Rotifera fauna; Keratella cochlearis; dam lake; Guluskur Bay; Turkey